Lateral flow immunochromatographic assay for rapid detection of dichlorvos residue in fruits and vegetables - Bao-Zhu Jia; Yan-Yan Liu; Feng-Yan Chen; Phannika Tongchai; Sumed Yadoung; Anurak Wongta; Zhen-Lin Xu; Lin Luo; Surat Hongsibsong (Food Chemistry: X)
Dichlorvos (DDVP), a widely used yet environmentally hazardous organophosphate pesticide, necessitates rapid field monitoring due to increasing regulatory restrictions. In this study, we firstly present a gold-nanoparticle-based lateral flow immunochromatographic assay (LFIA) employing a highly specific anti-DDVP monoclonal antibody for onsite DDVP detection within 20 min. The optimized LFIA exhibited exceptional analytical performance, with limits of detection spanning 16 μg/kg to 108 μg/kg across six fruit and vegetable matrices—all below the established maximum residue limits in foods. Method validation with spiked fruit and vegetable samples showed recovery rates of 87.3–109.4 % and 89.2–103.3 %, respectively, with coefficients of variation below 8.3 % and 7.9 %, respectively, confirming the accuracy and precision of the assay. Notably, LFIA exhibited good agreement with standard GC–MS/MS analysis when applied to 144 authentic samples, further validating its reliability for real-world applications. This LFIA offers key advantages including portability, cost-effectiveness, and compatibility with regulatory thresholds, making it an ideal alternative to conventional instrumental methods for routine pesticide residue screening in food safety supervision settings.